Interaction-oriented Instructional Practices Show Promise in Enhancing Overall Performance and Narrowing Racial Achievement Gaps in College Online Courses - Xu, Di; Avakian Orona, Gabe; Li, Qiujie (Online Learning, 2025)
Effective student interaction is critical for promoting student engagement and fostering a sense of community in online learning. Despite the extensive recognition of the importance of interaction-oriented practices in college online teaching, there is limited knowledge about how different types of interaction-oriented practices are related to student performance outcomes and, more importantly, racial equity gaps in those outcomes. This study addresses this gap by using a novel dataset that collected online teaching practices through a NSF-funded survey of close to 400 instructors at almost two dozen community colleges in a state. The survey data is further linked to the performance outcomes of nearly 10,000 students taught by these instructors. We begin by describing instructors’ use of practices that theory suggests are promising in promoting interactions and engagement in online classes. We further relate instructor teaching practices with student end-of-semester course performance and subsequent college persistence. The results indicate that greater engagement of interaction-oriented teaching practices relates positively and significantly to student course completion and grades. Additionally, practices aimed to promote instructor-student course management interactions are promising in reducing racial performance gaps. While teaching practices and the online learning landscape may have evolved post-COVID-19, the foundational strategies for effective interaction identified in this study remain relevant. These findings offer evidence-based strategies that can be adapted to current and future online learning environments, helping educators enhance student engagement and success in the post-pandemic era.